Project-Based Learning in Advanced Engineering Schools: Keeping Personal Education Ahead of the Curve - Anastasia D. Melnik; Anatolii V. Merenkov; Daniil G. Sandler (Интеграция образования)
Introduction. The discussion about project-based learning centers on the challenges of interrelation between higher education and the labor market and the development of proactive teaching methods in universities. Questions regarding the theory and methodology of project-based learning remain insufficiently explored, particularly concerning the alignment between learning and receiving sought-after specialists by employers, the integration of theory and practice within the educational process. The aim of this research is to analyze project-based learning programs developed by Russian universities and methods of their organization.